2017
DOI: 10.20869/auditf/2017/146/230
|View full text |Cite
|
Sign up to set email alerts
|

CSR organisational taxonomy and job characteristics on performance: SME case studies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…The findings of present study are aligned with past studies (Mayhew et al, 2007;Brown et al, 2014). A study conducted by Khin et al, (2017), confirmed the effect of job characteristics on employee performance. Similarly, the recent study Affandy (2016), revealed the impact of job characteristics on employee performance and they said if, the task is implemented in better manner then the positive outcomes can benefit to overall firm including the better employee performance.…”
Section: Discussion On Resultssupporting
confidence: 91%
“…The findings of present study are aligned with past studies (Mayhew et al, 2007;Brown et al, 2014). A study conducted by Khin et al, (2017), confirmed the effect of job characteristics on employee performance. Similarly, the recent study Affandy (2016), revealed the impact of job characteristics on employee performance and they said if, the task is implemented in better manner then the positive outcomes can benefit to overall firm including the better employee performance.…”
Section: Discussion On Resultssupporting
confidence: 91%
“…This is supported by a study from Hacman and Oldham (Frismandiri 2007) which states the factors that affect employee performance is the job characteristics. A study by [43] identifies factors affecting job performance, which include organizational structure, which comprises centralization and formalization, and job characteristics. The results conducted by [44] on the influence of job characteristics on employee performance indicates that job characteristics affect employee performance and show that if the task is well implemented, it will improve the real behavior that is shown in every person as a work achievement.…”
Section: Simultaneous Hypothesis Testing (F Test)mentioning
confidence: 99%